The Cortisol Levels, Histology, and Fine Structure of Various Tissues of Fish Gambusia affinis (Baird and Girard, 1853) after Exposure to Lead - Moh Awaludin Adam; Agoes Soegianto; Yenny Risjani; Carolyn Melissa Payus; R. Gunawan Pratama Yoga; Nina Hermayani Sadi; Evi Susanti; Ach Khumaidi; Ramli Ramli (Scientifica)
Background. Aquatic organisms demonstrate a high vulnerability to mortality when exposed to Pb, even at low concentrations. The objective of this investigation is to ascertain the histopathological alterations and cortisol concentrations in diverse tissues of Gambusia affinis, with a specific focus on the eggs and larvae, following exposure to varying concentrations of PbCl2. Methods. Adult specimens of G. affinis measuring 5-6 cm in length were obtained from a commercial fish breeding facility. A total of 8 fish with a 1 : 1 ratio of 4 pairs of broodstock were placed in an 8-liter aquarium. Following the adaptation phase, the broodstock underwent a spawning process that lasted for a duration of 7 days. Throughout the spawning process, assessments were conducted on the progression of the abdominal growth of the broodstock. Eggs ready to hatch and Gambusia larvae were taken and exposed to 0.1 mg/L PbCl2, 1 mg/L PbCl2, and control (without PbCl2) for 24 hours, with three replications. At the end of the experiment, histopathological analysis was conducted using the hematoxylin Ehrlich-eosin staining method and scanning electron microscopic (SEM) observation. The levels of Pb in gills were determined by employing atomic absorption spectrophotometer. The cortisol concentration in organ samples of fish was determined through the utilization of a cortisol ELISA Kit. Results. The findings of this investigation demonstrated an important bioaccumulation occurrence of Pb within the gills of Gambusia fish that were specifically subjected to 0.1 and 1 mg/L PbCl2. The histological structures of eggs and larvae that were subjected to PbCl2 exhibited impairment in comparison to the control group. The present study observed a significant elevation in cortisol levels among fish specimens that were subjected to PbCl2 exposure. Conclusions. The findings of this investigation suggest that the occurrence of Pb is linked to a rise in cortisol concentrations in various organs of G. affinis larvae. Furthermore, the research indicates that the exposure to Pb has a notable impact on the histological alterations in the eggs and larvae of Gambusia fish, implying that they are undergoing stress as a result of the Pb exposure.